2007
DOI: 10.1165/rcmb.2006-0385oc
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Inhaled Allergen Exposure Can Induce Persistent Tolerance

Abstract: Murine asthma models suggest that failure of immune tolerance rather than a defective T helper cell type 1 (Th1) immunity underlies the immune biology of Th2-driven allergen-induced airway disease. Intriguingly, prolonged exposures can result in a full waning of inflammation. The mechanisms underlying this observation are not understood. We hypothesized that the fading of inflammation is the result of regulatory processes, characterized by altered dendritic cell (DC)-T cell interactions. First, we implemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 36 publications
7
75
1
Order By: Relevance
“…A total of 1.25 3 10 3 washed BMDC were then added together with 1 3 10 5 purified CD4 + OVA-TCR transgenic T cells for 48 h, pulsed with [ T cell hyporesponsiveness in DLN and the airway mucosa that is mediated by a marked downregulation of allergen capture by AMDC subsets. These data are consistent with our and other studies showing induction of physiological and immunological tolerance after repeated exposure to innocuous allergens (11,13,16,38) and with a previous report that this process is dependent on the CCR7-guided migration of allergen-bearing DC to the DLN (18). We observed that inhaled aeroallergen is effectively captured by both CD11b hi and CD11b lo subsets of AMDC, equating to the CD103 2 and CD103 + DC subsets that have recently been described in both the lung and gut (3).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…A total of 1.25 3 10 3 washed BMDC were then added together with 1 3 10 5 purified CD4 + OVA-TCR transgenic T cells for 48 h, pulsed with [ T cell hyporesponsiveness in DLN and the airway mucosa that is mediated by a marked downregulation of allergen capture by AMDC subsets. These data are consistent with our and other studies showing induction of physiological and immunological tolerance after repeated exposure to innocuous allergens (11,13,16,38) and with a previous report that this process is dependent on the CCR7-guided migration of allergen-bearing DC to the DLN (18). We observed that inhaled aeroallergen is effectively captured by both CD11b hi and CD11b lo subsets of AMDC, equating to the CD103 2 and CD103 + DC subsets that have recently been described in both the lung and gut (3).…”
Section: Discussionsupporting
confidence: 94%
“…This model shares several features with other postsensitization models of inhalation tolerance developed in mice (15,16) and rats (14), including suppressed recruitment of effector CD4 + T cells and eosinophils into the airways and attenuated airways hyperresponsiveness through the promotion of Treg activity. We found that both CD11b hi CD103 2 and CD11b lo CD103 + AMDC captured inhaled OVA in vivo during the early onset of allergic inflammation, and that induction of inhalation tolerance markedly inhibited the capacity of AMDC subsets for aeroallergen capture.…”
Section: Endritic Cells (Dc)mentioning
confidence: 80%
See 1 more Smart Citation
“…immunization adsorbed to alum to achieve sensitization. Moreover, repeated airway administrations with OVA were shown to induce a gradual loss of the asthmatic phenotype in sensitized mice (34)(35)(36), although this effect is not Ag specific. We observed a limited reduction in eosinophilic airway inflammation in mice receiving two series of three OVA inhalations compared with mice that received only a single series of three OVAinhalation challenges ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Male mice (6-8 wk old) were exposed to OVA, as previously described (11). Briefly, mice were sensitized with 10 mg OVA (grade V; Sigma-Aldrich, Bornem, Belgium) adsorbed to 1 mg Al(OH) 3 (Sigma-Aldrich) i.p.…”
Section: Ova Exposure Modelmentioning
confidence: 99%